1997
DOI: 10.1016/s0735-1097(97)00049-1
|View full text |Cite
|
Sign up to set email alerts
|

Passivation of Metallic Stents After Arterial Gene Transfer of phVEGF165Inhibits Thrombus Formation and Intimal Thickening

Abstract: These findings indicate that arterial gene transfer of naked plasmid DNA encoding for an endothelial cell mitogen may successfully passivate endovascular stents by accelerating stent endothelialization, thereby reducing in-stent thrombus and obstruction due to intimal thickening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(69 citation statements)
references
References 39 publications
2
67
0
Order By: Relevance
“…8 -13 Furthermore, studies with both recombinant protein and arterial gene transfer demonstrate that VEGF enhances reendothelialization and thereby reduces intimal thickening in arterial restenosis and after stent implantation. 14,15 In the context of cardiac allograft arteriosclerosis, there are several mechanisms whereby VEGF may modulate migratory and proliferative responses of SMCs. As in restenosis, overexpression of VEGF may prevent intimal thickening by enhancing the regeneration and functional recovery of vascular endothelium damaged by ischemia-reperfusion injury and the alloimmune response.…”
mentioning
confidence: 99%
“…8 -13 Furthermore, studies with both recombinant protein and arterial gene transfer demonstrate that VEGF enhances reendothelialization and thereby reduces intimal thickening in arterial restenosis and after stent implantation. 14,15 In the context of cardiac allograft arteriosclerosis, there are several mechanisms whereby VEGF may modulate migratory and proliferative responses of SMCs. As in restenosis, overexpression of VEGF may prevent intimal thickening by enhancing the regeneration and functional recovery of vascular endothelium damaged by ischemia-reperfusion injury and the alloimmune response.…”
mentioning
confidence: 99%
“…Some studies showed that the administration of recombinant human VEGF in animals enhances the progression of the atherosclerotic plaque 23 , whereas others observed that it acts as an anti-atherosclerotic factor, promoting re-endothelization, reducing intimal thickening and preventing thrombus formation 5 .…”
Section: Discussionmentioning
confidence: 99%
“…VEGF, present in the vessel walls, promotes the proliferation of vascular endothelial cells and angiogenesis, but its role in atherosclerosis is still obscure. There are studies pointing to VEGF as a protection factor in the atherosclerotic plaque development, by acting as a regulator of the coronary artery wall endothelial integrity 4,5 . On the other hand, there are studies showing that neovascularization, mediated by VEGF, influences the pathogenesis of arterial diseases 6 .…”
Section: Introductionmentioning
confidence: 99%
“…34 Plastic sections were cut with a low speed diamond wafer mounted on the Buelher Isomet saw (Buelher, Evanston, IL, USA). Fiftym sections were cut and stained on one side with metachromatic stain.…”
Section: Evaluation Of Intimal Hyperplasiamentioning
confidence: 99%
“…Other homeobox genes have been shown to function as regulators of cellular differentiation and growth, 7,8 we have shown that overexpression of the Gax gene in normal rat carotid and rabbit iliac arteries can inhibit the fibro-proliferative response to balloon injury, 20,21 an effect that may be mediated by its ability to suppress integrin expression. 22 Adenovirus-mediated gene transfer performed in atheromatous vessels [23][24][25][26][27] combined with stent implantation [28][29][30][31][32][33][34] constitute two important challenges for clinical application. Here, we present the results of percutaneous adenovirus-mediated Gax gene transfer to atheromatous, stented rabbit iliac arteries in a clinical model of balloon angioplasty performed with the channel balloon catheter.…”
Section: Introductionmentioning
confidence: 99%